General Practitioner Preferences in Managing Care of Multiple Sclerosis Patients. (1st July 2015) - Bray, Mathieu; Wolfson, Christina; Moore, Fraser; Zhu, Bin; Uniat, Jennifer
Abstract: Background: Multiple sclerosis (MS) is a lifelong neurological disorder requiring care in a variety of settings. The purpose of this study is to describe preferences of general practitioners (GPs) with regards to providing care for MS patients. Methods: A stratified sample of 900 GPs in the province of Quebec were sent a questionnaire, with 266 returning completed questionnaires. Respondents were surveyed about their preferences using four clinical scenarios describing hypothetical patients experiencing different stages of MS. Respondents were asked whether they would continue managing the patient themselves, formally refer the patient to a specialist, or seek specialist advice. Results: In two scenarios representing stable courses, 40.9% and 61.6% of GPs, respectively, intended to manage the patient themselves. GPs who reported having experience with MS patients were more likely to report an intention to continue management. In one scenario, GPs operating in rural areas were less likely to consider management than those in the Montreal metropolitan area (odds ratio=0.422, 95% confidence interval 0.20-0.90). Conclusions: For MS patients with a stable disease course, an important proportion of GPs appear to be willing to manage long-term care for MS patients. RÉSUMÉ: Préférences des médecins généralistes concernant la prise en charge des patients atteints de sclérose en plaques. Contexte : La sclérose en plaques (SP) est une maladie neurologique qui nécessite des soins tout au long de la vie, dans plusieurs contextes. Le but de cette étude était de décrire les préférences des médecins généralistes (MG) concernant les soins à prodiguer aux patients atteints de SP. Méthode : Un questionnaire a été envoyé à un échantillon stratifié de 900 MG de la province de Québec. Deux cent soixante-six questionnaires complétés ont été retournés. Le questionnaire portait sur leurs préférences évaluées au moyen de quatre scénarios cliniques décrivant des patients hypothétiques à différents stades de la SP. On demandait aux répondants s'ils continueraient à traiter le patient eux-mêmes, s'ils référeraient le patient à un spécialiste ou s'ils demanderaient conseil auprès d'un spécialiste. Résultats : Dans deux scénarios où l'état du patient était stable, 40, 9% et 61, 6% des MG respectivement avaient l'intention de traiter eux-mêmes le patient. Les MG qui rapportaient qu'ils avaient de l'expérience dans le traitement des patients atteints de SP étaient plus susceptibles de rapporter qu'ils avaient l'intention de continuer à traites le patient. Dans un scénario, les MG travaillant en milieu rural étaient moins susceptibles de considérer traiter le patient eux-mêmes que ceux qui travaillaient dans la région métropolitaine de Montréal (rapport de cotes=0, 422 ; intervalle de confiance de 0, 20 à 0, 90). Conclusions : Une importante proportion des MG semble disposée à suivre à long terme les patients atteints de SP dont la maladie est stable.